Pengaruh Suasana Cafe, Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pelanggan Pada Shan’s Juice Cafe di Karawang - Ramadhan, Salsa Regita; Isyanto, Puji; Sumarni, Neni (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to see the effect of cafe atmosphere, service quality and location both partially and simultaneously on customer satisfaction at Shan's Juice Café in Karawang. This type of research uses a quantitative approach where the research population is Shan's Juice Café customers with a sample of 100 respondents obtained using non-probability sampling techniques. Data collection methods use questionnaires and direct reviews. The method for data analysis applied is multiple linear regression and SPSS version 27.0 instruments. The results of this study indicate that cafe atmosphere, service quality and location partially and simultaneously have a positive and significant effect on customer satisfaction at Shan's Juice Café in Karawang.